Friday

March 6, 2015

March 6, 2015

Posted by **Anonymous** on Wednesday, December 5, 2012 at 1:36pm.

- joool -
**Steve**, Wednesday, December 5, 2012 at 3:43pm3(y^2 - xy - 2x^2) = 0

3(y-2x)(y+x) = 0

y=2x or y = -x

**Answer this Question**

**Related Questions**

Derive - Find the derivative of sin(2x + 3y)= 3xy + 5y-2. I have this so far 1) ...

Algebra-Please check my answers - Posted by Jessie on Monday, October 18, 2010 ...

Algebra-Please check my answers - Posted by Jessie on Monday, October 18, 2010 ...

Math help polynomial - multiply the following polynomial -3x(y^2+2y^2) answer ...

bobpursly, - Is this correct now after i revised it Multiply. 3xy^2(5xy-4x+6y) ...

Math! - 1) What is the value of 19 + 5a^4 + 3b^2 when a = 2 and b = -4? (this ...

Math - I have no clue how to do this as no values were given and im confused. ...

differential equations - the directions are to determine whether or not the ...

Algebra - Are these complete? m^2 + 4mn +4n^2 = (m + 2n)(m+2n) 3x^3y^2 – 3x^2y^2...

Math - How do you factor: 9x^2y^3 - 3x^3y^2 - 15xy i got: 3xy(3xy^2 - x^2y - 5) ...